ANALYSIS OF THE INFLUENCE OF ATTRIBUTE DESIGN TO CONVERSION OF THE USE OF GOFOOD AND GRABFOOD APPLICATION SERVICES BY MUSLIM CONSUMER IN INDONESIA - Krisrana, Athaya Vita; Gayatri, Gita (ASEAN Marketing Journal, 2023)
Manuscript type: Research Article. Research Aims: The main objective of this study is to examine the factors that affect the conversion on the food delivery application services, namely Gofood and Grabfood in Indonesia. Design/methodology/approach: Mixed method by conducting focus group discussion and distributing questionnaires. Data analysis was done by using covariance based Structural Equation Modelling (SEM). Research Findings: Based on the result of the FGD, there are other variables that are considered to have an influence on the conversion, namely payment design so that the latent variables studied in this study visual design, information design, navigation design, payment, and collaboration design. Based on quantitative data analysis, the output shows that information design, navigation design, payment design and collaboration design affect the conversion of Gofood and Grabfood service usages. However, the visual design does not affect the conversion of the use of Gofood and Grabfood by Muslim consumers in Indonesia. Theoretical Contribution/Originality: This study adds one variable that affects conversion, namely payment design Practitioner/Policy Implication: For managerial that who take cares of the service usage to improve halal features in the form of filter or sign that indicates halal at a restaurant or merchant, require each restaurant or merchant to explain the composition of the food ingredients used, improve the quality of navigation design and add payment alternative that will increase the collaboration of the using the services. Research limitation/Implications: Demography, number of samples, difference test on Gofood and Grabfood services Keywords: Conversion, visual design, informational design, navigational design, payment design, collaboration design, mixed-method, Gofood.